Effect of cobalt on nickel oxide toward reduction behaviour in hydrogen and carbon monoxide atmosphere - Dzakaria N.; Abu Tahari M.N.; Saidin S.; Tengku Saharuddin T.S.; Salleh F.; Lahuri A.H.; Yarmo M.A. (Trans Tech Publications Ltd, 2024)
Indexed by SCOPUS/ERA